Pengembangan Kualitas Kompetensi Kognitif Siswa Melalui Assesment Profiling Gaya Belajar Menurut Bobbi DePorter dan Mike Hernacki - Muhammad Zikri Abdillah; Nur Azmi Wiantina; Desi Setiadi (Ghaidan: Jurnal Bimbingan Konseling Islam dan Kemasyarakatan, 2024)
Students have various learning styles, based on this, teachers must work hard in providing lessons. Sometimes teachers complain because the lesson material provided does not seem easy for students to accept. Therefore, as a result, there needs to be countermeasures to overcome this problem, namely by recognizing the learning style of each student. Learning style profiling assessments analyze how students like and understand learning material. To ensure that students' learning styles can develop as expected, teaching strategies must be adapted to various student learning styles. Therefore, by using a learning style profiling assessment, teachers must know the learning styles desired by students because by knowing them, teachers will be able to understand and have strategies that are considered most appropriate for delivering learning in the classroom. This research was conducted at Al-Ihsan Middle School, Jakarta. The research method used is the Four D (4-D) development model which is reduced to 3-D, namely define, design and develop. The population of this research was 30 students in class VIII of Al-Ihsan Middle School, Jakarta. The results of this research illustrate that class VIII students at Al-Ihsan Middle School, Jakarta, have a variety of learning styles, namely 34.50% visual, 35.17% auditory and 30.33% kinesthetic. If teachers can recognize and understand students' learning style tendencies, then it will be very valuable in knowing the extent to which students have achieved cognitive competence.